Effects of Si-doping on structural, electrical, and optical properties of polar and non-polar AlGaN epi-layers. (August 2016) - Yang, Hongquan; Zhang, Xiong; Wang, Shuchang; Wang, Yi; Luan, Huakai; Dai, Qian; Wu, Zili; Zhao, Jianguo; Cui, Yiping
Abstract: The polar (0001)-oriented c -plane and non-polar ( 11 2 ¯ 0 ) -oriented a -plane wurtzite AlGaN epi-layers were successfully grown on polar (0001)-oriented c -plane and semi-polar ( 1 1 ¯ 02 ) -oriented r -plane sapphire substrates, respectively with various Si-doping levels in a low pressure metal organic chemical vapor deposition (MOCVD) system. The morphological, structural, electrical, and optical properties of the polar and non-polar AlGaN epi-layers were studied with scanning electron microscopy (SEM), X-ray diffraction (XRD), Hall effect, and Raman spectroscopy. The characterization results show that Si dopants incorporated into the polar and non-polar AlGaN films induced a relaxation of compressive residual strain and a generation of biaxial tensile strain on the surface in consequence of the dislocation climbing. In particular, it was found that the Si-induced compressive strain relaxation in the non-polar AlGaN samples can be promoted by the structural anisotropy as compared with the polar counterparts. The gradually increased relaxation of compressive residual strain in both polar and non-polar AlGaN samples with increasing Si-doping level was attributed to the Si-induced enhancement in the opportunity for the dislocations to interact and annihilate. This implies that the crystal quality for both polar and non-polar AlGaN epi-layers can be remarkably improved by Si-doping. Highlights: The non-polar ( 11 2 ¯ 0 ) -oriented a -plane AlGaN epi-layers were grown by MOCVD. Si-induced strain relaxation in the non-polar AlGaN epi-layers can be promoted. The crystal quality for both AlGaN epi-layers can be improved by Si-doping. Si-doping efficiency of AlGaN samples was degraded at SiH4 flow rate of 40 sccm.